Changes of pedaling technique and muscle coordination during an exhaustive exercise - Dorel, S.; Drouet, J. M.; Couturier, A.; Champoux, Y.; Hug, F. (Medicine & Science in Sports & Exercise, 2009)
Purpose: Alterations of the mechanical patterns during an exhaustive pedaling exercise have been previously shown. We designed the present study to test the hypothesis that these alterations in the biomechanics of pedaling, which occur during exhaustive exercise, are linked to changes in the activity patterns of lower limb muscles.